MAXIM OF PERSUASIVE LANGUAGE IN WRITTEN DISCOURSE IN THE PUBLIC SPACE OF NKRI - RDTL BORDER - Nalenan, Joni Soleman; Seran, Yanuarius (Universitas Hamzanwadi, 2020)
This study aimed to determine what maxims were contained in written discourse in the public space of NKRI - RDTL border areas. The theory used to solve the problem in this study is the sociopragmatic theory. The method used is a qualitative descriptive method. The research data were grouped into four components, namely the political component, the commercial component, the health component, and the education component. Data related to the political component tended to have political nuances. Commercial component data refers to service offerings, services and product purchases. Health component data were related to stakeholder recommendations regarding prevention and self-protection from Covid-19. The education component data found in this study came from various levels of education units that promote their existence to get new students. Based on the sociopragmatic theory, the research results show that there are six maxims in the persuasive language of written disc ourse in the public space of NKRI - RDTL border areas, namely maxim of wisdom, maxim of sympathy, maxim of generosity, maxim of manner, maxim of relevance, and maxim of quality.